An interactive tool for rapid biventricular analysis of congenital heart disease. (17th November 2015) - Gilbert, K.; Lam, H.‐I.; Pontré, B.; Cowan, B. R.; Occleshaw, C. J.; Liu, J. Y.; Young, A. A.
Summary: Cardiac malformations are the most common birth defect. Better interventions in early life have improved mortality for children with congenital heart disease, but heart failure is a significant problem in adulthood. These patients require regular imaging and analysis of biventricular (left and right ventricular) function. In this study, we describe a rapid method to analyse left and right ventricular shape and function from cardiac MRI examinations. A 4D (3D+time) finite element model template is interactively customized to the anatomy and motion of the biventricular unit. The method was validated in 17 patients and 10 ex‐vivo hearts. Interactive model updates were achieved through preconditioned conjugate gradient optimization on a multithread system, and by precomputing points predicted from a coarse mesh optimization.